Prudence and prevention: empirical evidence - Mayrhofer, Thomas; Schmitz, Hendrik (Economics letters, 2025)
Theory shows that optimal prevention decisions in the sense of self-protection (i. e., primary prevention) depend not only on the level of (second-order) risk aversion but also on prudence (third-order risk aversion). We use a unique dataset that combines data on higher-order risk preferences and observed real-world preventive behavior and provide the first representative evidence of a negative relationship between prudence and self-protection: We find that prudent individuals in the high-risk group (above the age of 60 or chronically ill) indeed invest less in self-protection as measured by influenza vaccination. This does not hold for younger and healthy individuals for whom influenza vaccination rates are low in general.
Online verfügbar: 13. Oktober 2025, Artikelversion: 16. Oktober 2025
Gesehen am 01.12.2025